Assessment of Lead and Cadmium Concentrations in Raw Cow Milk from Farms near Namanve Industrial Park in Kira Division, Wakiso District, Uganda - S. Biryomumaisho; A. Atukwase; L. Manirakiza (Journal of Applied Sciences and Environmental Management, 2022)
Lead and Cadmium concentrations were analysed in raw cow milk samples collected from smallholder zero grazing households near Namanve Industrial Park in Kira Division in Wakiso district near Kampala city, Uganda. The concentration of heavy metals in milk was tested with atomic absorption spectrophotometry using the Perkin Elmer AAA Model 2380 after acid digestion. The overall mean concentration of lead and cadmium was 0.01 and 0.0083 mg/kg respectively. Of the three wards, Bweyogerere had the highest lead concentration (0.014mg/kg) and cadmium (0.011mg/kg). Analysis of Variance (ANOVA) test of the mean concentrations of lead between and within wards showed significant differences (F = 10.85, P < 0.05) and the findings were similar for cadmium (F=4.77, P < 0.05). Multiple comparison tests (Bonferroni) showed Bweyogerere raw milk had significantly higher lead concentration than milk from Kireka (P=0.008) and milk from Kirinya (P < 0.0001) and also significantly higher cadmium concentration than milk from Kirinya (P = 0.0009). Mean concentration of each metal residue was below the recommended minimum hazardous intake in diet as per Codex/Uganda National Bureau of Standards at 0.02 mg/kg for both lead and cadmium. Therefore, milk from cows reared around Namanve presents no public health-related lead and cadmium hazards.